Influences of Project Management Capabilities on the Organizational Performance of the Saudi Construction Industry - Sulieman, H. A.; Alfaraidy, F. A. (Engineering, Technology & Applied Science Research, 2019)
This paper aims to study the relations between construction enterprises’ project management capabilities and organizational performance. A questionnaire survey was administered to 89 Saudi construction contracting organization administrative members. Data were obtained from 32 projects that were held during the last two years and were analyzed using structural equation modeling (SEM). It was hypothesized in this study that a construction organizational performance is influenced by project management capabilities within the enterprise. A structural equation model was set up to measure the above two latent variables through their constituent variables. This study introduced a method to measure performance both in qualitative and quantitative terms. The strong path coefficients between the constructs of the model are an indication that after decades in pursuit of finding ways to improve the performance of construction organizations, subjective dimensions of performance have proven to be as effective as the traditional objective dimensions.